The velocity of ovis in prehistoric times: the sheep bones from Early Neolithic Lameiras, Sintra, Portugal - Davis, Simon (2017)
Excavations at Early Neolithic and Late Neolithic Lameiras near Sintra in Portugal have uncovered numerous caprine bones. Many, including milk teeth, humeri, metapodials, calcanea, astragali and terminal phalanges, can be securely identified using well established morphological criteria and osteometrical differences on metacarpal condyles and astragali. Radiocarbon dates on some of these sheep bones indicate their presence in southern Portugal around 5,450 cal BC which is the beginning of the Early Neolithic in this region. It is possible that the change from hunting to husbanding occurred rapidly. Current evidence from the Near East, the region whence our domesticated sheep came, indicates a date of domestication there that is some three thousand years earlier. In other words sheep coming overland must have travelled quite rapidly – perhaps too rapidly – and so it seems likely that livestock were being shipped already in the Neolithic.